Burnout syndrome and alcohol consumption in prison employees - Campos, Juliana Alvares Duarte Bonini (2016)
Objective: The aims of this study were to estimate the association between an at‑risk drinking pattern and sociodemographic variables, and to compare the mean scores of the factors associated with the Burnout Syndrome, according to the alcohol consumption pattern in staff members from two Brazilian prisons. Methods: A cross‑sectional study was developed with 339 participants (response rate = 63.8%). The instruments used were a sociodemographic questionnaire, the Alcohol Use Disorders Identification Test (AUDIT), and the Maslach Burnout Inventory – General Survey (MBI‑GS). Results: The participants’ average age was 40.2 (SD = 8.8) years, and 81.0% were male. Among 78.5% of participants (95%CI 74.1 – 82.8) reported consuming alcoholic beverages. The prevalence of at‑risk drinking behavior in the sample was 22.4% (95%CI 18.0 – 26.9), and of the Burnout Syndrome was 14.6% (95%CI 10.8 – 18.4). We observed a significant association between at‑risk drinking behavior with gender, higher risk for men (OR = 7.32, p < 0.001), smoking, increased risk for smokers (OR = 2.77, p < 0.001), and religious practice, showing lower risks for religion practitioners (OR = 0.364, p < 0.001). We noticed significantly higher mean scores (p < 0.001) of emotional exhaustion and cynicism, and lower scores of professional achievement among individuals who reported consuming alcoholic beverages. Conclusion: Men who smoke were more likely to develop an at‑risk drinking pattern, while religion is presented as a protective factor. Individuals who consume alcohol were more affected by the different factors of the Burnout Syndrome.